Non-enclosure methods for non-suspended microalgae cultivation: literature review and research needs - Katarzyna, Ledwoch; Gu, Sai; Avijeet Singh, Oinam (Elsevier, 2015)
Microalgae are getting more interests from industry and science communities. Applications of these small, unicellular microorganisms are countless: from fourth generation biofuels, through fish feed to pharmaceuticals. Ordinary methods of cultivation may be associated with many problems such as high costs, high energy consumption, and low product yield. It is difficult to control contaminations in open ponds while photobioreactors are mainly at laboratory scale and expensive to scale-up. Scientists are investigating various methods of microalgae cultivation and processing to overcome those problems. One of the novel approaches is the non-suspended method for microalgae culturing, where microalgae are grown on attached surfaces. Growing microalgae on surfaces is an attractive option and showing promising results. In comparison with ordinary suspended photobioreactors, the attached systems offer higher biomass yields, easy to scale-up with better light distribution within the reactor and better control of contamination. Moreover, the consumption of water can be drastically reduced. So far, there is not enough research for this method. Limited studies have been reported on enclosure mode of this approach with algae encapsulation into matrix. It is found that this mode would be difficult to scale up due to high costs of the enclosure material and difficulty of separating microalgae from matrix. Non-enclosure mode is more promising way of non-suspended cultivation. So far, no work has been carried out to conduct non-suspended culturing with the use of aeroterrestrial microalgae. They are species growing on the surfaces at highly humid environments. Using them in attached cultivation systems could potentially lower the water consumption to minimum. Studies have shown that the biomass of lower water content can be produced if compared to non-suspended cultivation methods. In addition, mechanization of the cultivation and harvesting processes would be less complex, as the product will not be immersed in the liquid. There would be no need for glass reactors, as lights can be placed in the spaces between surfaces. The light distribution is predicted to be the highest among all existing methods, as there would be no free floating particles absorbing and reflecting light. It will only need humid conditions, rich in CO2 between attachment surfaces. To evaluate potential advantages for non-suspended culturing of aeroterrestrial microalgae in non-enclosure way, proper experiments need to be conducted. In this review, basic concepts of attached cultivation system are discussed, focusing on the studies of biofilm formation including factors affecting deposition and systems. The detailed description of aeroterrestrial microalgae is included to give insight into potential applications of the species into attached cultivation systems.
Keywords: Aeroterrestrial; Biofuels; Cultivation; Microalgae; Non-enclosure; Non-suspended